If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying abs(7x + -4) = abs(4x + -8) Reorder the terms: abs(-4 + 7x) = abs(4x + -8) (-4 * abs + 7x * abs) = abs(4x + -8) (-4abs + 7absx) = abs(4x + -8) Reorder the terms: -4abs + 7absx = abs(-8 + 4x) -4abs + 7absx = (-8 * abs + 4x * abs) -4abs + 7absx = (-8abs + 4absx) Solving -4abs + 7absx = -8abs + 4absx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '8abs' to each side of the equation. -4abs + 8abs + 7absx = -8abs + 8abs + 4absx Combine like terms: -4abs + 8abs = 4abs 4abs + 7absx = -8abs + 8abs + 4absx Combine like terms: -8abs + 8abs = 0 4abs + 7absx = 0 + 4absx 4abs + 7absx = 4absx Add '-4absx' to each side of the equation. 4abs + 7absx + -4absx = 4absx + -4absx Combine like terms: 7absx + -4absx = 3absx 4abs + 3absx = 4absx + -4absx Combine like terms: 4absx + -4absx = 0 4abs + 3absx = 0 Factor out the Greatest Common Factor (GCF), 'abs'. abs(4 + 3x) = 0Subproblem 1
Set the factor 'abs' equal to zero and attempt to solve: Simplifying abs = 0 Solving abs = 0 Move all terms containing a to the left, all other terms to the right. Simplifying abs = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(4 + 3x)' equal to zero and attempt to solve: Simplifying 4 + 3x = 0 Solving 4 + 3x = 0 Move all terms containing a to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 3x = 0 + -4 3x = 0 + -4 Combine like terms: 0 + -4 = -4 3x = -4 Add '-3x' to each side of the equation. 3x + -3x = -4 + -3x Combine like terms: 3x + -3x = 0 0 = -4 + -3x Simplifying 0 = -4 + -3x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| x^3+8x-4=0 | | a^2*x^3-1/8*a^2*(1+x)^3 | | 0.5+7y=-25 | | 4(x-1)-(5-2x)=5 | | 6(x-3)+1=10 | | 2(X-10)=70 | | C=A(150c) | | 3(5x+8)=375 | | a^2x^3-1/8a^2*(1+x)^3 | | x^3+8x+2=0 | | 9(w+3)=5w-13 | | y=1.23x+0.19x^2 | | 6x=4(5-x) | | 7(1-4b)=231 | | 7x^2+2sqrt(14)x+2=0 | | 4x+5x-9=2 | | 7-8(-6+8k)=119 | | 2x(3x-1)=5x+1 | | -5(5-8r)+4r=-113 | | 15x-2x+7=9+15-4x | | 4(x-3)=7 | | -3(4-4a)+a=92 | | 5x^2-5x=14 | | 4(-6+8v)=-120 | | F(4)=2 | | F(4)=y | | 4(6+8v)=-120 | | t+3/4=7/8 | | -8(5+3x)=-160 | | 0.15=4.5 | | 4x(27x)=50 | | 12(3x+4)-6(2x-2)=4x-60 |